Características morfofuncionais de estruturas ovarianas e diagnóstico precoce de gestação em ovelhas - RIZZONI, Leandro L. B. (2018)
The use of biotechniques in animal reproduction allows to provide the improvement of the herd, however it is necessary to know the reproductive physiology, which has been better elucidated through ultrasound and hormonal dosing techniques, thus enabling a better accuracy in the techniques of reproductive manipulation and diagnostic imaging. The present study was divided into two experiments. The experiment 1, aimed to establish a relationship between the vascular, morphological and functional pattern of the corpus luteum (CL) of sheep through color Doppler (CD) ultrasonography. Therefore, 34 Dorper crossbred ewes with Santa Inês were randomly divided into G1 (ruffed) and G2 (mated) that had estrus synchronized. Ultrasonographic images of CLs were made daily up to the day D17, by the transrectal route. The analyzed variables were the CL area and the blood flow area (FS). Blood samples were collected for P4 dosing. The CL area had a progressive increase to D5 (P<0.0001), without significant increase on subsequent days, G1 progressed to a marked fall in its area from D13 (P<0.0001). The same pattern was observed for FS area, with progressive growth up to D4 (P<0.0001) followed by a drop in D13 (P<0.0001) for G1. The plasma concentrations of P4 reached physiological values for sheep up to D6 (P<0.0001), with a pronounced drop in D12 (P<0.0001) for G1. Experiment 2, aim to determine the reliability of Doppler ultrasonography, as a predictive diagnosis of non-pregnant sheep 17 days after coverage, through the vascular pattern of the corpus luteum. 62 Dorper crossbred sheep were used with Santa Inês. The diagnosis of pregnancy in D17 (DG17), classified the animals as Pregnant, for those who presented some area of blood flow (FS) in the corpus luteum (CL) and Non-pregnant, for those who did not present any FS area in CL. In D30 the diagnosis of gestation (DG30) was confirmed by B-mode ultrasonography. DG30 was compared retrospectively with DG17. The diagnostic performance parameters based on the FS area had a sensitivity of 100.0%; specificity of 80.0%; negative predictive value 100.0%; positive predictive value of 73.3% and accuracy of 87.1%. The proportion of false positive was 12.9% (8/62), caused by long cycles and early embryonic losses, and the false negative rate was 0.0% (0/62). These studies have demonstrated that the use of ultrasound in CD mode offers additional advantages in B-mode ultrasound and is a potential tool for the evaluation of luteal function and for the early diagnosis of gestation in sheep, allowing a better accuracy in the identification and measurement of the corpus luteum and its vascularization.